2011
DOI: 10.1111/j.1479-828x.2010.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sublingual versus vaginal misoprostol for second-trimester pregnancy termination: A meta-analysis

Abstract: Sublingual and vaginal misoprostol are safe and effective for mid-trimester pregnancy termination. The differences obtained between both routes probably do not have clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Hou et al, (2010) have compared one and two day intervals and have determined that a 2-day mifepristone-misoprostol interval resulted in fewer incomplete abortions than a 1-day interval for second trimester termination of pregnancy. Misoprostol historically has been administered vaginally in the second trimester, but a meta-analysis of published randomised controlled trials that compared sublingual and vaginal routes concluded that the sublingual route shortened the induction-foetal expulsion interval and was the route preferred among women and staff (Cabrera et al, 2011). No statistically significant differences between treatment groups were observed for placental retention or for side effect except for fever, which was more common in the vaginal group; the preferred route is therefore sublingual.…”
Section: Induction With Mifepristone and Misoprostolmentioning
confidence: 88%
“…Hou et al, (2010) have compared one and two day intervals and have determined that a 2-day mifepristone-misoprostol interval resulted in fewer incomplete abortions than a 1-day interval for second trimester termination of pregnancy. Misoprostol historically has been administered vaginally in the second trimester, but a meta-analysis of published randomised controlled trials that compared sublingual and vaginal routes concluded that the sublingual route shortened the induction-foetal expulsion interval and was the route preferred among women and staff (Cabrera et al, 2011). No statistically significant differences between treatment groups were observed for placental retention or for side effect except for fever, which was more common in the vaginal group; the preferred route is therefore sublingual.…”
Section: Induction With Mifepristone and Misoprostolmentioning
confidence: 88%
“…10 The results were also comparable to study done by Cabrera Y et al who found the sublingual route shortened the induction-fetal expulsion interval (4.54, 95% CI -8.03 to -1.05) and was the route preferred among women. 11 In a study conducted by Devendra Singh Kushwaha et al concluded that sublingual route of administration was more acceptable than the oral route (X 2 = 6.78, P = 0.009, d.f. = 6).…”
Section: Discussionmentioning
confidence: 99%
“…In order to relieve them, we need to minimize the number of hospital visits or hospital stay and this consideration is also meaningful in terms of expenses [16,17]. According to previous reports, when misoprostol was administered the probability of the successful spontaneous expulsion of the fetal sac within 24 hours was around 80%, but it is practically diffi cult to wait for 24 hours after the administration of the drug [18]. One of the reasons is that outpatient follow-up after the vaginal insertion of misoprostol may result in abdominal pain or vaginal bleeding at an unpredictable time and this may cause many troubles to the patient and guardian including admission to the emergency room.…”
Section: Discussionmentioning
confidence: 99%